IMPROVING TIME EFFICIENCY USING COMPUTER SOFTWARE INTENDED FOR PRODUCTIVE PREPARATION IN CUSTOM-MADE CABINET FURNITURE FACTORIES (Natural Resources and Technology, 2024)
The goal of the research presented in this paper is to see the impact of computer software intended for manufacturing preparation on the time required to prepare the complete technical documentation during the launch of a new product within a micro enterprise for the production of custom-made cabinet furniture. For that purpose, the time spent during standard constructive preparation was measured. Standard constructive preparation covers views, sections and details drawing in AutoCAD of previously prepared 3D models of various pieces of furniture, and then dimensioning the constituent elements and creating a scheme for cutting the material in an appropriate software. For the same pieces of furniture, time was measured during the preparation of the same documentation through several different software intended for constructive preparation, specifically in PolyBoard in this part of the research, as presented in this paper. The results show that the computer software significantly shortens the constructive preparation time.
Keywords: PolyBoard, interactive software, furniture design, constructive preparation, manufacturing methods